Analisis Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada potek Dinda Farma Di Klaten - Darusman, Idfah; , Drs. Farid Wajdi, M.M., Ph.D (2015)
The aim of this study was to determine the effect of service quality dimensions consisting of (tangible, reliability, responsiveness, assurance and empathy) on customer loyalty in the pharmacy Dinda Farma in Klaten. This study also aims to determine simultaneously the influence of the five dimensions contained in the independent variable on the dependent variable and to know the dimensions of which peling dominant influence among the five dimensions contained in the independent variable on the dependent variable. This type of research is a quantitative research, with a population of customers in pharmacy Dinda Farma with a sample of 90 people. Purposive sampling or based on certain characteristics. Research data collection techniques through a questionnaire with Likert scale. T test variables obtained through tangible and responsiveness not significantly affect customer loyalty variable, while the variable reliability, assurance, empathy significantly affect customer loyalty variable. In the F test results showed a significant probability that in this study the dimensions of independent variables jointly affect the dependent variable. The coefficient of determination obtained a yield of 0.442 means that the dimensions of tangible, reliability, responsiveness, assurance and empathy on service quality variables can explain the variable customer loyalty by 0.442 or 44.2%, the rest can be explained by other variables that are not included in the model. Keywords: tangible, reliability, responsiveness, assurance, empathy, service quality and customer loyalty